Improving Communication Skills Through Psychology: A Qualitative Study on Active Listening, Cultural Sensitivity, and Role-Playing Techniques among Undergraduate Students - Mehrad, Aida (UIN Raden Mas Said Surakarta, 2025)
Effective communication is a fundamental aspect of human interaction, impacting personal relationships, academic engagement, and professional success. In psychology education, it is crucial to equip students not only with theoretical knowledge but also with practical communication strategies that are adaptable to various cultural and social contexts. This study explores how undergraduate psychology students perceive the role of communication in their personal, academic, and future professional lives, as well as the impact of a semester-long course titled